Peer review of the pesticide risk assessment for the active substance sulfoxaflor in light of confirmatory data submitted. (28th March 2019) - ; Abdourahime, Himdata; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Ctverackova, Lucie; De Lentdecker, Chloe; Ippolito, Alessio; Kardassi, Dimitra; Messinetti, Silvia; Molnar, Tunde; Saari, Katri Elina; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessment carried out by the competent authority of the co‐rapporteur Member State the Czech Republic for the pesticide active substance sulfoxaflor are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory ecotoxicology data. The conclusions were reached on the basis of the evaluation of the representative uses of sulfoxaflor as an insecticide on fruiting vegetables (field and greenhouse application), cucurbits (field and greenhouse application), spring and winter cereals (field application) and cotton (field application). The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. For the field and non‐permanent structure greenhouses, a high risk to honeybees and bumble bees was identified related to some pertinent scenarios (treated crop scenario except after flowering period, weed scenario, field margin scenario). A low risk was concluded for honeybees, bumble bees and solitary bees in case of permanent structure greenhouse provided the low exposure in such scenarios.